Early and Long-Term Results of Minimally Invasive Mitral Valve Repair in Young and Middle-Aged Patients - Tsvyk, Andrii S.; Gorbatiuk, Volodymyr I.; Krykunov, Kostiantyn O.; Yemets, Glib I.; Telehuzova, Oleksandra V.; Chernetskyi, Yevhen O. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To analyze the early and long-term results of minimally invasive mitral valve repair in young and middle-aged patients and compare the outcomes with mitral valve repairs performed through standard sternotomy. Materials and methods. From 2016 to 2021, 128 patients with mitral insufficiency were operated in the Ukrainian Children’s Cardiac Center. Exclusion criteria included patients under 18 or over 59 years old and patients with concomitant pathology of the aortic valve, aorta, and coronary arteries. Results. In the investigated group, the average duration of cardiopulmonary bypass and aortic cross-clamping time was longer than in the comparative group. However, the average duration of mechanical ventilation, average time in theintensive care unit, and average length of hospitalization were shorter in the investigated group. Patients in the investigated group less frequently required red blood cell transfusion (5.6% vs. 14.6%) and plasma transfusion (9.4% vs. 14.6%). The percentage of postoperative complications was almost half lower in the investigated group (3.6% vs. 6.6%). None of the patients in the investigated group showed a severe degree of mitral insufficiency, while two patients in the comparative group had severe mitral insufficiency. Conclusions. Minimally invasive mitral valve repair is associated with a lower percentage of postoperative complications. Early and long-term observation results indicate the high effectiveness and safety of the minimally invasive method.